Thermal Cracking of Jatropha Oil with Hydrogen to Produce Bio-Fuel Oil - Yi-Yu Wang; Chia-Chi Chang; Ching-Yuan Chang; Yi-Hung Chen; Je-Lueng Shie; Min-Hao Yuan; Yen-Hau Chen; Li-Xuan Huang; Cesar Augusto Andrade-Tacca; Do Van Manh; Min-Yi Tsai; Michael Huang (Energies, 2016)
This study used thermal cracking with hydrogen (HTC) to produce bio-fuel oil (BFO) from jatropha oil (JO) and to improve its quality. We conducted HTC with different hydrogen pressures (PH2; 0–2.07 MPa or 0–300 psig), retention times (tr; 40–780 min), and set temperatures (TC; 623–683 K). By applying HTC, the oil molecules can be hydrogenated and broken down into smaller molecules. The acid value (AV), iodine value, kinematic viscosity (KV), density, and heating value (HV) of the BFO produced were measured and compared with the prevailing standards for oil to assess its suitability as a substitute for fossil fuels or biofuels. The results indicate that an increase in PH2 tends to increase the AV and KV while decreasing the HV of the BFO. The BFO yield (YBFO) increases with PH2 and tr. The above properties decrease with increasing TC. Upon HTC at 0.69 MPa (100 psig) H2 pressure, 60 min time, and 683 K temperature, the YBFO was found to be 86 wt%. The resulting BFO possesses simulated distillation characteristics superior to those of boat oil and heavy oil while being similar to those of diesel oil. The BFO contains 15.48% light naphtha, 35.73% heavy naphtha, 21.79% light gas oil, and 27% heavy gas oil and vacuum residue. These constituents can be further refined to produce gasoline, diesel, lubricants, and other fuel products.